PENGARUH PERENCANAAN PAJAK, RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN - Harimurti, Fadjar; Kristianto, Djoko; Nurul ’Aini, Annisa (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
The purpose of this study was to analyze the effect of tax planning, return on assets and debt to equity ratio to the value of companies incorporated in LQ45 on the Indonesia Stock Exchange in 2014 - 2017. This type of research is an empirical study of companies incorporated in LQ 45 shares listed on the Indonesia Stock Exchange in 2014 - 2017. Samples of 35 companies used purposive sampling technique. The data collection method used documentation. Data analysis techniques used multiple linear regression. The results showed that tax planning had a positive and significant effect on the company value of companies incorporated in LQ45 on the Indonesia Stock Exchange in 2014 - 2017. Return on assets has a positive and significant effect on the value of companies incorporated in LQ45 on the Indonesia Stock Exchange in 2014 - 2017. Debt to equity ratio has a positive and significant effect on the value of companies incorporated in LQ45 on the Indonesia Stock Exchange in 2014 - 2017.